2020
DOI: 10.2147/opth.s253689
|View full text |Cite
|
Sign up to set email alerts
|

<p>Non-Penetrating Deep Sclerectomy versus Trabeculectomy in Primary Congenital Glaucoma</p>

Abstract: Purpose: To evaluate the safety and efficacy of non-penetrating deep sclerectomy with a collagen implant versus trabeculectomy in primary congenital glaucoma. Subjects and Methods: This was a retrospective interventional comparative nonrandomized clinical study that included 80 eyes of 80 children presenting with primary congenital glaucoma under the age of 3 years. Forty eyes have undergone non-penetrating deep sclerectomy (NPDS) and the other 40 eyes have undergone penetrating trabeculectomy. The main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…14 The outcomes of NPDS have been compared with those of other procedures to treat PCG. 15,16 However, to our knowledge, no studies have compared the outcomes of NPDS between surgeries performed by trainees vs experienced ophthalmologists. In this study, we compared the success rates of NPDS performed by trainees vs experienced ophthalmologists, and evaluated the determinants of success 6 months after NPDS in Saudi pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…14 The outcomes of NPDS have been compared with those of other procedures to treat PCG. 15,16 However, to our knowledge, no studies have compared the outcomes of NPDS between surgeries performed by trainees vs experienced ophthalmologists. In this study, we compared the success rates of NPDS performed by trainees vs experienced ophthalmologists, and evaluated the determinants of success 6 months after NPDS in Saudi pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nonpenetrating deep sclerectomy (NPDS) is an alternative filtering surgery. Compared with Trab, NPDS has a higher safety, but is more technically demanding (5). It was designed to reduce the resistance of aqueous humor outflow by removing the outer wall of Schlemm's canal and the external part of the adjacent trabecular meshwork tissue, while avoiding penetrating the anterior chamber (6).…”
Section: Introductionmentioning
confidence: 99%
“…Elhofi et al 38 reported the outcomes in 80 eyes of 80 children with primary congenital glaucoma. Forty eyes underwent deep sclerectomy, and 40 eyes had a trabeculectomy.…”
Section: Surgical Treatmentmentioning
confidence: 99%